The Migration Patterns and Identity of the Okun-Yoruba People of Central Nigeria - Ilesanmi Akanmidu Paul (Yoruba Studies Review)
Migration is a global phenomenon. From time immemorial, man has been moving from one place to another for temporary or permanent settlements. This is largely facilitated by natural or artificial factors. The former include natural disasters such as ecological change and draught, while the latter can be instigated by wars and search for better fortunes. This study examines the nature of the movements of the Okun-Yoruba people from the western region of Nigeria to the confluence of the Niger and Benue rivers in the Central Geographical Zone of Nigeria. It reveals how their long years of interactions with peoples of the confluence region were aided by the European delimitation of the area as part of the North, which has been the basis of sociopolltical agitation. The study reveals that Okun-Yoruba people, despite their geographical delimitation as northerners, see themselves more as southerners.